A framework for the assessment of MPA effectiveness based on life history of fishes. (December 2015) - Batista, Marisa I.; Henriques, Sofia; Pais, Miguel P.; Cabral, Henrique N.
Abstract: Changes in ecosystems structure and function due to the high impacts human pressures on oceans have led to the increasing numbers of Marine Protected Areas (MPA), since MPA are widely accepted as adequate tools to protect, maintain, and restore ocean ecosystems. Increases in density, size and biomass of organisms within protected areas have often been found. However, their worldwide effectiveness is compromised by the interaction of several factors, such as inadequate conduction of processes (e.g. due to political reasons) and the common lack of appropriate scientific datasets to support planning and management decisions. This study proposes a framework for assessing the potential effectiveness of an already implemented MPA and identifying major gaps. The framework is based on three components: species–habitat association, species' life history and functional groups and pressures affecting the MPA. The potential of the MPA to support the lifecycle of fish species was assessed in order to identify effective management actions. The theoretical framework was applied to Arrábida MPA (Portugal) in order to exemplify its practical results. Arrábida MPA showed potential to support the lifecycle of most species, although some key life phases (spawning and nursery) are not efficiently protected by the actual limits/level of protection of the MPA, namely for some of the most important fisheries' target species. This framework is particularly useful as an alternative or a complementary support to early decisions for MPA management and the identification of priority actions needed to ensure the accomplishment of initial objectives or the suitability of their adaptation. This approach can be implemented in MPA worldwide, although the accuracy of results will be closely related with the quality of input data. The present framework can contribute to improve the effectiveness of global MPA networks and to fulfill international conservation targets, such as OSPAR, Convention for Biological Diversity and European Natura 2000 network. Highlights: Appropriate scientific datasets to support MPA planning and management decisions are uncommon. A framework for the assessment of MPA effectiveness was developed. The framework is based on species–habitat association, species life history and pressures affecting habitats. The potential of MPA to support the lifecycle of fish species is assessed to identify effective management actions. The theoretical framework was applied to Arrábida MPA to exemplify its practical results.